(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
Palm shell has great potential as an adsorbent material due to its porosity and thermal stability, but its high moisture content can affect its surface area and absorption capacity. This study aims to optimize the drying process of palm shells to enhance their adsorption performance by applying an exponential model. The drying process was carried out at a temperature of 80°C with time variations ranging from 1 to 6 hours. Parameters measured included wet and dry moisture content, Moisture Ratio (MR), and drying rate. The results showed that drying the palm shell for 4 hours yielded the best results, with a reduction in wet moisture content by 19-21% and dry moisture content by 23-28%. The exponential model analysis provided drying rate constants for the three samples of 0.0443, 0.0238, and 0.0159, respectively. The measured MR graph compared with the model predictions showed a very good fit, with an R² value close to 1, meaning the exponential model is effective in predicting the drying rate. Adsorption performance was tested using a Dylon dye solution with a concentration of 25 ppm, where the palm shell was able to adsorb up to 85% of the dye within 180 minutes.